2000
DOI: 10.1046/j.1365-2567.2000.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro treatment of human transforming growth factor‐β1‐treated monocyte‐derived dendritic cells with haptens can induce the phenotypic and functional changes similar to epidermal Langerhans cells in the initiation phase of allergic contact sensitivity reaction

Abstract: SUMMARYHuman monocyte-derived dendritic cells (MoDCs) obtained from peripheral blood monocytes (PBMC) cultured with granulocyte±macrophage colony-stimulating factor (GM-CSF) and interleukin-4 (IL-4) can be activated in vitro by a variety of simple chemicals such as haptens and several metals. Recently, it has been demonstrated that transforming growth factor-b 1 (TGFb 1 ) can induce further differentiation of MoDCs to the cells that share some characteristics with epidermal Langerhans cells, i.e. they contain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 37 publications
(47 reference statements)
8
45
1
1
Order By: Relevance
“…The establishment of human in vitro models of DC had offered the possibility to demonstrate that haptens were able to directly activate cultured DC derived from peripheral blood monocytes or from CD34 + HPC (Aiba et al, 1997;Degwert et al, 1997;Rougier et al, 2000;De Smedt et al, 2001;Weigt et al, 2004). Several studies confirmed these observations showing the upregulation of maturation markers (CD83, CD80, CD86, CD40) on human DC (Coutant et al, 1999;Aiba et al, 2000;Tuschl et al, 2000;Arrighi et al, 2001). Cytokine production such as IL-12p40, TNF-α, and IL-1β has also been reported upon hapten stimulation (Aiba et al, 1997(Aiba et al, , 2003De Smedt et al, 2001).…”
Section: Use Of Dcs To Identify Contact Allergensmentioning
confidence: 93%
“…The establishment of human in vitro models of DC had offered the possibility to demonstrate that haptens were able to directly activate cultured DC derived from peripheral blood monocytes or from CD34 + HPC (Aiba et al, 1997;Degwert et al, 1997;Rougier et al, 2000;De Smedt et al, 2001;Weigt et al, 2004). Several studies confirmed these observations showing the upregulation of maturation markers (CD83, CD80, CD86, CD40) on human DC (Coutant et al, 1999;Aiba et al, 2000;Tuschl et al, 2000;Arrighi et al, 2001). Cytokine production such as IL-12p40, TNF-α, and IL-1β has also been reported upon hapten stimulation (Aiba et al, 1997(Aiba et al, , 2003De Smedt et al, 2001).…”
Section: Use Of Dcs To Identify Contact Allergensmentioning
confidence: 93%
“…This hapten increases the expression of DC surface markers essential for antigen presentation, such as the molecules of the major histocompatibility complex class II and costimulatory molecules (4)(5)(6)(7)(8)(9)(10) and increases chemokine production and chemokine receptor expression (11)(12)(13)(14) , thereby favoring antigen presentation. In DC, contact sensitizers activate mitogen-activated protein kinases (15)(16)(17)(18)(19)(20)(21) . We previously have reported that nickel sulfate activates the transcription nuclear factor kappa B (NF-kB) and the transcription factor activator protein-1 (AP-1) and induces the expression of inducible isoform of nitric oxide synthase (iNOS) in mouse skin DC (22) .…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of in vitro differentiated primary DCs is difficult due to the nature of these cells such as low numbers in the source and donor-todonor variability [2]. In addition, treatment with several cytokines is generally applied to obtain DCs from blood or bone marrow cells [3,11,30], and this process probably changes the cell reactivity to stimulations. Thus, established cell lines are preferable to standardize the condition among assay.…”
Section: Discussionmentioning
confidence: 99%